2002
DOI: 10.1016/s0963-8687(02)00018-5
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthiness in electronic commerce: the role of privacy, security, and site attributes

Abstract: While the growth of business-to-consumer electronic commerce seems phenomenal in recent years, several studies suggest that a large number of individuals using the Internet have serious privacy concerns, and that winning public trust is the primary hurdle to continued growth in e-commerce. This research investigated the relative importance, when purchasing goods and services over the Web, of four common trust indices (i.e. (1) third party privacy seals, (2) privacy statements, (3) third party security seals, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
535
3
42

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 887 publications
(608 citation statements)
references
References 28 publications
28
535
3
42
Order By: Relevance
“…Furthermore, 87% of the players reported that they preferred to play on the "biggest named" sites, as they believed that cheating was less likely. Studies of Web sites in general have found that specific design features play a critical role in influencing the perceived trustworthiness of a site, including the ease of navigation (Cheskin-Sapient, 1999), the clarity in financial transactions (Nielsen, Molich, Snyder, & Farrell, 2000), the extent to which the Web site has a professional look and feel (Belanger, Hiller, & Smith, 2002;Kim & Stoel, 2004), and the appropriate use of visual design elements (Kim & Moon, 1998). Mixing advertisements and content will diminish trust (Jenkins, Corritore, & Wiedenbeck, 2003), as will poor Web site maintenance (Nielsen et al, 2000).…”
Section: Journal Of Gambling Issues: Issue 21 July 2008mentioning
confidence: 99%
“…Furthermore, 87% of the players reported that they preferred to play on the "biggest named" sites, as they believed that cheating was less likely. Studies of Web sites in general have found that specific design features play a critical role in influencing the perceived trustworthiness of a site, including the ease of navigation (Cheskin-Sapient, 1999), the clarity in financial transactions (Nielsen, Molich, Snyder, & Farrell, 2000), the extent to which the Web site has a professional look and feel (Belanger, Hiller, & Smith, 2002;Kim & Stoel, 2004), and the appropriate use of visual design elements (Kim & Moon, 1998). Mixing advertisements and content will diminish trust (Jenkins, Corritore, & Wiedenbeck, 2003), as will poor Web site maintenance (Nielsen et al, 2000).…”
Section: Journal Of Gambling Issues: Issue 21 July 2008mentioning
confidence: 99%
“…Lastly, internet privacy and security relatively affected e-trust (Kim, 2003). Several studies (Belanger, Hiller, & Smith, 2002;Kim & Shim, 2002) have found that security is predictor of consumer intention to shop via online. This was due to the fact that many e-consumers are unwilling to provide personal information over the internet (Salisbury et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A precondition for online shops to be a good alternative for consumers is that consumers can trust the information online shops provide about the characteristics of the merchandise, payment conditions, delivery process, privacy and security (Belanger et al 2002;OECD 2011). Customers of online shops fully depend on the information on the website, while customers of normal (physical) shops can gather information on the quality of products by actually experiencing (e.g., seeing, hearing, feeling) products before making a purchase decision.…”
Section: Regulation Of E-commercementioning
confidence: 99%
“…This does not mean, however, that online sellers always have an incentive to be as informative as possible. Online sellers in particular have an incentive to design their online shop to maximize consumer expenditures (Belanger et al 2002). So, regulatory intervention might be needed to realize full transparency in online consumer markets.…”
Section: Regulation Of E-commercementioning
confidence: 99%